Combined JWST-MUSE integral field spectroscopy of the most luminous quasar in the local universe, PDS 456 - Seebeck, Jerome; Veilleux, Sylvain; Liu, Weizhe; Rupke, David S. N.; Vayner, Andrey; Wylezalek, Dominika; Zakamska, Nadia L.; Bertemes, Caroline (The astrophysical journal, 2024)
Fast accreting, extremely luminous quasars contribute heavily to the feedback process within galaxies. While these systems are most common at cosmic noon (z ∼ 2), here we choose to study PDS 456, an extremely luminous (L bol ∼ 1047 erg s−1) but nearby (z ∼ 0.185) quasar where the physics of feedback can be studied in greater detail. We present the results from our analysis of the JWST MIRI/Medium Resolution Spectroscopy (MRS) integral field spectroscopic (IFS) data of this object. The extreme brightness of PDS 456 makes it challenging to study the extended emission even in this nearby object. MIRI/MRS instrumental effects are mitigated by using complementary NIRSpec and MUSE IFS data cubes. We show clear evidence of a multiphase gas outflow extending up to 15 kpc from the central source. This includes emission from warm molecular (H2 ν = 0-0 and 1-0) and ionized (e.g., Paα, [O iii], [Ne iii], and [Ne vi]) gas with typical blueshifted velocities down to −500 km s−1. We are also able to probe the nuclear dust emission in this source through silicate and polycyclic aromatic hydrocarbon emission features but are unable to spatially resolve it. Our results are consistent with this powerful quasar driving a radiatively driven wind over a broad range of distances and altering the ionization structure of the host galaxy.
Gesehen am 30.06.2025